Mapping Public Interest in Cryptocurrency in Indonesia (2021–2024): Analyzing Geographical Disparities and Temporal Trends - Wawan Gunawan; Debashish Sharma (Blockchain, Artificial Intelligence, and Future Research, 2025)
This study investigates public interest in cryptocurrency in Indonesia, focusing on related queries, geographical distribution, and temporal trends. Utilizing a quantitative descriptive approach with secondary data from Google Trends (January 2021–December 2024), the findings reveal that cryptocurrency is predominantly perceived as a trading tool, with terms like trading and crypto dominating search queries. Geographical analysis highlights significant regional disparities, with Bali demonstrating the highest interest due to its global connectivity and digitally literate population, while Nusa Tenggara Timur reflects challenges such as limited infrastructure and financial literacy. Temporal trends show fluctuations aligned with global market events and regulatory developments, stabilizing in 2023–2024 as public perceptions matured. These results emphasize the need for public education to broaden understanding beyond speculative trading and for inclusive strategies to address regional and educational gaps. This study contributes to the literature by offering a novel framework integrating geographical and temporal analyses, providing actionable insights for policymakers and stakeholders to foster equitable and sustainable cryptocurrency adoption in emerging markets.